2020
DOI: 10.1113/jp279042
|View full text |Cite
|
Sign up to set email alerts
|

Ablating the Rab‐GTPase activating protein TBC1D1 predisposes rats to high‐fat diet‐induced cardiomyopathy

Abstract: Key pointsr Although the role of TBC1D1 within the heart remains unknown, expression of TBC1D1 increases in the left ventricle following an acute infarction, suggesting a biological importance within this tissue.r We investigated the mechanistic role of TBC1D1 within the heart, aiming to establish the consequences of attenuating TBC1D1 signalling in the development of diabetic cardiomyopathy, as well as to determine potential sex differences. r TBC1D1 ablation increased plasma membrane fatty acid binding prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
(148 reference statements)
0
3
0
Order By: Relevance
“…TBC1D1, and its homolog TBC1D4, are key RabGAPs regulating muscle glucose utilization. In murine skeletal muscle, TBC1D1 appears to control exercise endurance [ 31 ], and its ablation is associated with high-fat diet-induced diastolic dysfunction, left ventricular fibrosis and cardiac hypertrophy [ 32 ]. Increased transcription of TBC1D1 was also observed in L6 skeletal myoblasts overexpressing LANCL1 or LANCL2 [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…TBC1D1, and its homolog TBC1D4, are key RabGAPs regulating muscle glucose utilization. In murine skeletal muscle, TBC1D1 appears to control exercise endurance [ 31 ], and its ablation is associated with high-fat diet-induced diastolic dysfunction, left ventricular fibrosis and cardiac hypertrophy [ 32 ]. Increased transcription of TBC1D1 was also observed in L6 skeletal myoblasts overexpressing LANCL1 or LANCL2 [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…notably, the inhibitory roles of rabGaPs and rasGaPs in cardiac hypertrophy have previously been reported (15)(16)(17)(18). The ablation of the rabGaP TBC1 domain family member 1 results in significant cardiac hypertrophy in male rats and increased myocardial damage after ischemia/reperfusion (15,16). Similarly, depletion of carabin, another rabGaP, can exacerbate cardiac hypertrophy and significantly reduce fractional shortening in mice (17,18).…”
Section: Introductionmentioning
confidence: 92%
“…GTPase-activating proteins (GaPs) can induce inactivation of small GTPases by inducing GTP hydrolysis (13,14). notably, the inhibitory roles of rabGaPs and rasGaPs in cardiac hypertrophy have previously been reported (15)(16)(17)(18). The ablation of the rabGaP TBC1 domain family member 1 results in significant cardiac hypertrophy in male rats and increased myocardial damage after ischemia/reperfusion (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…HFD induced obesity leads to the characteristics of T2D, which in turn leads to DCM (Barbeau et al, 2020). DCM is characterized by functional and structural abnormalities, including myocardial dysfunction, myocardial cell death, myocardial fibroblast activation, and metabolic disorders.…”
Section: Phenomenon and Harm Of Pyroptosis In Obese/dyslipidemic Animalsmentioning
confidence: 99%
“…The mechanism of myocardial cell death induced by these cytokines is mainly related to oxidative and/or nitridation injury. Studies have found that specific superoxide inhibitors can completely block cytokine-induced cardiomyocyte death, so inhibiting cardiomyocyte death can effectively intervene in DCM.HFD induced obesity leads to the characteristics of T2D, which in turn leads to DCM(Barbeau et al, 2020). DCM is characterized by functional and structural abnormalities, including myocardial dysfunction, myocardial cell death, myocardial fibroblast activation, and metabolic disorders.…”
mentioning
confidence: 99%